The Financial Performance of the English Football Clubs - Rompotis, Gerasimos G (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
The financial performance of twenty English football clubs over the period 2013-22 is examined in this study with correlation and panel data analysis. Three performance measures are used: Return on Assets (ROA), Return on Equity (ROE), and Profit Margin. The size of clubs and their liquidity, leverage, efficiency, cash flow efficiency, and turnover per employee are employed as explanatory variables of performance. Sporting data, including attendance rate, the number of wins, the uncertainty in the Premier League, participation in the Premier League or not, and the presence in UEFA’s European club competitions, are also assessed. The empirical findings accentuate a positive relationship between performance and liquidity, efficiency, cash flow efficiency, and revenue per employee. The opposite is the case for leverage. Wins are positively related to ROA, while the opposite relationship is found for the uncertainty factor. Finally, the presence of clubs in the Premier League is positively associated with their financial performance